2020
DOI: 10.1111/asj.13394
|View full text |Cite
|
Sign up to set email alerts
|

Carcass traits and meat quality of Texel lambs raised in Brachiaria pasture and feedlot systems

Abstract: Increasing demands for healthy and eco-friendly products and processes concerned with animal well-being have stimulated consumer interest in pasture finishing systems for lambs (Jacques, Berthiaume, & Cinq-Marsa, 2011). This feeding system affects animal growth rate, carcass weight and yield, muscle: fat ratio, and meat lipid profile, which can reflect in sensorial characteristics such as flavor, odor, and softness (Carrasco et al., 2009). Blackburn, Snowder, and Glimp (1991) reported lower amounts of fat in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
1
16
0
1
Order By: Relevance
“…Feeding regimes have a significant effect on sheep's carcass quality (Prache et al, 2021), and, as reported in previous findings (da Silva et al, 2020;Morales Gómez et al, 2021), this study also found that Black Tibetan sheep raised indoors with composite forage diet had the best carcass quality. This had been attributed to a lower A/P ratio in the rumen alongside a combination of higher energy intake and lower energy expenditure (Boughalmi and Araba, 2016).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Feeding regimes have a significant effect on sheep's carcass quality (Prache et al, 2021), and, as reported in previous findings (da Silva et al, 2020;Morales Gómez et al, 2021), this study also found that Black Tibetan sheep raised indoors with composite forage diet had the best carcass quality. This had been attributed to a lower A/P ratio in the rumen alongside a combination of higher energy intake and lower energy expenditure (Boughalmi and Araba, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…In order to protect grassland ecosystem in China as well as meet an increasing demand for high quality Black Tibetan sheep's meat, the animals' feeding regimes have gradually transitioned from traditional grazing to intensive feeding. This changed approach can significantly protect the ecological environment, shorten the slaughtering time and greatly increase the quantity of sheep in a short time (da Silva et al, 2020). However, such changes in feeding regimes also affect the overall health, growth characteristics and even the meat quality of sheep due to differences in diet composition (Boughalmi and Araba, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The content of a lamb's diet influences the composition and value of its tissues ( 36 ). Furthermore, several trials have indicated that numerous feeding approaches can facilitate the deposition of n-3 LC PUFA in muscle tissues in lambs, resulting in healthier meat ( 16 , 24 , 37 42 ). The use of vegetable seed oils in ruminant diets was found to increase energy and the level of UFA deposited in meat ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The profile and quality of fatty acids in lamb can be improved by incorporating lipid sources into the diet of lot-fed lambs to boost the levels of omega-3 long-chain polyunsaturated fatty acids (n-3 LC PUFA) known to be beneficial for human health ( 14 , 15 ). Meat industry producers and processors aim at producing heavy carcasses of young animals with good musculature, supplying desired meat cut yields and an attainable fat layer to protect carcasses while in cold storage ( 16 ). Intramuscular fat (IMF), fat melting point (FMP), and pH are essential quality indicators of red meat ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the goal of beef sheep production is to obtain carcasses with a greater amount of muscle and fat levels that are not excessive yet sufficient to guarantee the juiciness and flavor of the meat (Urbano et al, 2017). The main characteristics studied in carcass evaluation are weight, yield, state of greasiness, and conformation (Oliveira et al, 2017;Silva et al, 2018), while the factors that determine carcass quality are genotype, sex, age, rearing system, and health (Ekiz et al, 2012;Hopkins & Mortimer, 2014;Silva et al, 2020). Another important point to be evaluated in the production of sheep meat is the quality of the meat, which includes the characteristics of color, tenderness, and proximate composition (Santos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%